A Polymorphism Within the MBP Gene Is Associated With a Higher Relapse Number in Male Patients of Multiple Sclerosis - Espino-Paisán, Laura; Agudo-Jiménez, Teresa; Rosales-Martínez, Isabel; López-Cotarelo, Pilar; García-Martínez, María Ángel; Domínguez-Mozo, María Inmaculada; Pérez-Pérez, Silvia; Dieli-Crimi, Romina; Comabella, Manuel; Urcelay, Elena; Álvarez-Lafuente, Roberto (Frontiers in Immunology, 2020)
Myelin basic protein (MBP) is thought to be one of the key autoantigens in multiple sclerosis (MS) development. A recent study described the association of the single nucleotide polymorphism (SNP) rs12959006, within the MBP gene, with a higher risk of relapse and worse prognosis. We aim at studying potential associations of this SNP to MS in an independent population. Clinical data of the first 5 years of the disease were collected retrospectively from 291 MS confirmed patients. MBP polymorphism rs12959006 was genotyped in all patients. Associations with EDSS, number of relapses and serology for Herpesvirus 6 (HHV-6) and Epstein Barr (EBV) viruses were studied. Lymphocyte activation measured by CD69 expression was also analyzed according to sex and rs12959006 genotype. The rs12959006 polymorphism contributed significantly to a higher number of relapses at 5 years after onset only in male patients (rs12959006∗TT β = 0.74 [0.36–1.09]; p = 7 × 10–5). Titers of anti-HHV6 IgG antibodies showed also a mild association with relapses, both in male and female patients (β = 0.01 [0.01–0.02]; p = 3.7 × 10–8). Both the genetic variation in MBP and HHV-6 infection aid in predicting a higher number of relapses during the first years of MS. The association described in MBP rs12959006∗T is exclusive to male patients.